On the adequacy of evapotranspiration estimate using Priestly-Taylor's approach (2006)
The measurement of potential evapotranspiration ET 0 using Priestly – Taylor (P-T) formula in humid tropical region was carried out at Shasha along Ojoo- Moniya road, Akinyele Local Government in the Ibadan Metropolitan Area of Oyo State, Nigeria. The difficulty and limitations of obtaining weather and vegetation input data in most of the evapotranspiration (ET) empirical formula are overcame in the P-T equation that is based more on physical parameters than being purely empirical. ET 0 estimation of the study location was evaluated for two months using 1973 - 2002 daily climatological data obtained from a nearby weather station. The P-T method gave poor R2 values of 0.056 and 0.167 for July and August 2004. However, an adjusted P-T model values gave R2 values of 0.949 and 0.986 respectively. Validating the adjusted P- T model using year 2000 daily weather data of the study location for July and August gave R2 values of 0.905 and 0.915. The P-T; model efficiency in computing evapotranspiration was 62.3% for July and 49.2% for August. The findings indicate that the adjusted P-T model is a good method of ET0 estimation in the humid tropics where there is dearth of input data, and even when available, the data are usually expensive to obtain for research purposes.